Exploring the Effect of Unemployment on Crime Rates Among Youth in Mukono Central Division, Mukono district - Karen White Kipwola (Uganda Christian University, 2023)
The study's goal was to investigate how youth crime rates in Mukono Central Division, Mukono District, are affected by unemployment. The study's goals included assessing the factors that contribute to youth unemployment and its causes, examining the effects of unemployment on crime rates, and developing strategies to lower both rates. The study employed the use of a cross-sectional research design which involved the use of both qualitative and quantitative research approaches. The sample totaled 118 individuals, including unemployed youth, police officers, division political leaders, the town clerk, the mayor, and a community development officer. These were deliberately and randomly selected. Information was gathered via questionnaires, focus group discussion guides, and interview guides. Thematic content analysis was used to examine the qualitative data, and SPSS was used for statistical analysis. According to study findings, the main causes of youth unemployment and the variables influencing it in Mukono Central Division are skill mismatches between the educational system and employers' expectations, restricted access to financial capital, insufficient or lack of skills to join the informal sector, and rural-urban migration. It also demonstrated that youth unemployment leads to destitution, which later encourages criminal activity as a means of income, that high unemployment rates are "push factors" for young people to join gangs and commit robberies or participate in political violence, that the lack of options for legal employment forces youth to engage in illegal activities, and that youth inaction, which lengthens the period of unemployment, contributes to an increase in violent crimes. These are the key conclusions. In the end, it was determined that education, the introduction of welfare benefits specifically for unemployed youth, the participation of unemployed youth in entrepreneurial training and skills development, and the government's commitment to combating youth unemployment by launching programs like youth funds are the main ways to reduce youth unemployment and wrongdoings in Mukono Central Division. However, it can be inferred from the study's results that unemployment has an impact on juvenile misbehavior in Mukono Central Division.
This is a dissertation.